Pengaruh Litbang, Industri dan Perguruan Tinggi Terhadap Minat Generasi Muda Bekerja di Sektor Keantariksaan dengan Pendekatan Triple Helix Network - Intan Perwitasari; Agil Sutrisnanto (STI Policy and Management Journal, 2015)
Partnership in human resource development can not be separated from the role of aerospace science and technology actors through space education and mindedness. The partnership aims to reduce lag of technology in the industry, R & D and higher education. One of the strategic issues in human resources elements is low interest of young people to work in space sector. With reference to the concept of an ideal partnership R & D in the National Innovation System, then the question is how effective the role of actors in science and technology in growing interest of young generation amid human resource needs encouragement and regeneration. This study aimed to analyze that the effect of relationship variables of R & D, industry and higher education to the interest of the young generation in Indonesia space sector. The method of analysis used was Partial Least Square (PLS), by taking a sample of 139 respondents conducted in four universities with purposive sampling method and triple helix network analysis. Results of treatment with SmartPLS is no positive effect variable space research, space industry, higher education to interest in the young generation. It is caused by low coordination between space research, space industry and higher education to built capacity buiding in joint research. Space research likes LAPAN has been given mandate to build space education, and to be a design center of space technology for industry.